Conceptions of Spirituality and Religiosity among university students in the Medical Program at PUC Goiás (Research, Society and Development, 2025)
The concept of religion is widely debated across academic fields, particularly between essentialist perspectives, which view religion as a universal and unchanging reality, and constructivist perspectives, which define it as a social and cultural phenomenon. This theoretical debate underscores the importance of examining the plurality of religious traditions and conceptions of spirituality among contemporary youth, who increasingly adhere to religious pluralism and the “no religion” category. This study aimed to assess the spiritual conceptions of medical students aged 18 to 30 at the Pontifical Catholic University of Goiás (PUC Goiás). An observational, descriptive, and analytical epidemiological survey was conducted with 33 students using an in-person questionnaire. Results showed that 81.8% of participants identified with a religion, with Catholicism being the most prevalent (45.5%); however, 33% of these students had not attended a religious institution for more than six months. Additionally, 12.1% declared having “No Religion,” and 27.3% reported expressing their spirituality in non-conventional ways. Overall, the findings reveal a shift in the traditional religious profile of PUC Goiás medical students, marked by reduced institutional affiliation and diverse forms of spiritual expression, with many maintaining a personal and less formal connection to Christian faith.